Real-time application of the PROBFLO framework risk approach as a part of the digital twin towards the implementation of environmental flows in the Limpopo Basin, southern Africa - O’Brien, G. C.; Wade, M.; Bembe, M. J.; Dickens, Christopher; McNiel, T.; Retief, H.; Silva, Paulo; Garcia Andarcia, Mariangel (International Water Management Institute, 2024)
The natural world consists of various complex physical, biological and social systems that are connected and interact with each other. New technological developments are improving the ability of the managers of our natural resources, to understand and contribute to the way we are developing using and sometime abusing our resources. Through the Digital Twin for management of water resources in the Limpopo River Basin we have an opportunity to integrate available sustainable environmental flows and water resource management technology into an integrated system, that will allow stakeholders of the Limpopo River and surrounding regions to understand, monitor and manage these resources for current and future generations.